DEVELOPMENT OF SPECIFIC PHYSICAL QUALITIES IN SKILLED VOLLEYBALL PLAYERS - Jo‘rayev, Abdinaim Xudoynazarovich (Mental Enlightenment Scientific-Methodological Journal, 2025)
Nowadays, many researchers focus solely on analyzing the execution and improvement of passing techniques in volleyball. However, it is emphasized that there is no effective and transparent system for selecting (recruiting) talented young athletes in volleyball. This lack of a structured selection process prevents the formation of a strong sports reserve and the preparation of high-level athletes for national teams. Identifying the key physical qualities of volleyball players and studying their development during their athletic progression is of scientific interest. This article explores the development of specific physical qualities in skilled volleyball players across different playing positions. It also highlights innovative approaches to training that integrate physical culture, physical education, health improvement, physical development, and the promotion of a healthy lifestyle to foster well-rounded, physically and morally developed individuals.